Nanomedicine Based Drug Delivery Systems Recent Developments and Future Prospects - Shakeel, Faiyaz (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint entitled "Nanomedicine Based Drug Delivery Systems: Recent Developments and Future Prospects" contains 14 articles in total. This includes one editorial, ten research articles, and three review articles. All articles are associated with nanomedicine-based drug delivery systems for the solubility, bioavailability, and therapeutic enhancement of active drug molecules. In recent years, there has been a tremendous amount of research on nanomedicine-based drug delivery systems. This reprint has brought together prominent scientists who have explored a diverse range of applications of nanomedicine-based drug delivery systems. I believe that further clinical and toxicological studies on both animal and human models are still required to explore the complete potential and commercial exploitation of nanomedicine-based drug delivery systems. The diverse and critical perspectives within this reprint provide sufficient information on the development, characterization, and evaluation of nanomedicine-based drug delivery systems.